Linezolid and Vancomycin Decrease the Therapeutic Effect of Methylene Blue‐Photodynamic therapy in a Mouse Model of MRSA Bacterial Arthritis. (19th February 2013) - Tanaka, Masamitsu; Mroz, Pawel; Dai, Tianhong; Huang, Liyi; Morimoto, Yuji; Kinoshita, Manabu; Yoshihara, Yasuo; Shinomiya, Nariyoshi; Seki, Shuhji; Nemoto, Koichi; Hamblin, Michael R.
Abstract: We previously reported that photodynamic therapy (PDT) using intra‐articular methylene blue (MB) could be used to treat arthritis in mice caused by bioluminescent methicillin‐resistant Staphylococcus aureus (MRSA) either in a therapeutic or in a preventative mode. PDT accumulated neutrophils into the mouse knee via activation of chemoattractants such as inflammatory cytokines or chemokines. In this study, we asked whether PDT combined with antibiotics used for MRSA could provide added benefit in controlling the infection. We compared MB‐PDT alone, systemic administration of either linezolid (LZD) alone or vancomycin (VCM) alone or the combination of PDT with either LZD or VCM. Real‐time noninvasive imaging was used to serially follow the progress of the infection. PDT alone was the most effective, whereas LZD alone was ineffective and VCM alone showed some benefit. Surprisingly the addition of LZD or VCM reduced the therapeutic effect of PDT alone ( P < 0.05). Considering that PDT in this mouse model stimulates neutrophils to be antibacterial rather than actively killing the bacteria, we propose that LZD and VCM might inhibit the activation of inflammatory cytokines without eradicating the bacteria, and thereby reduce the therapeutic effect of PDT. Abstract : Mouse bacterial arthritis caused by bioluminescent MRSA can be treated by injection of methylene blue into the knee joint and illumination with red light. When the PDT was combined with anti‐MRSA antibiotics the effectiveness was less, rather than more as expected. This may be due to the action of antibiotics in reducing the inflammatory response stimulated by PDT that causes an influx of neutrophils that actually kill the bacteria.